Efektifitas Latihan Aerobik pada Keseimbangan Jalan Penderita Parkinson’s Disease: Meta-Analisis - Fadli, Arif; Noerdjanah, Noerdjanah (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Parkinson's disease (PD) has caused progressive gait impairment with a high risk of falls in daily activities. Aerobic exercise is effective in improving physical fitness with an impact on cognitive function of gait execution. The benefits of aerobic exercise have not been optimally utilized by PD sufferers. Objectives: This systematic review study aims to know effect of aerobic training exercises on gait balance in PD patients. This study will synthesize article data from randomized control trial (RCT) studies in 5 electronic databases PubMed, Google-Scholar, PEDro, OVID, and ScienceDirect. Article searches using search keywords: "Parkinson's disease" AND (exercise OR training OR "dance exercise" OR "aerobic exercise" OR "treadmill exercise"). Methods: The researcher used the Revman 5.3 program to meta-analysis data with an effect size of value Cohen's d. 334 PD patients in 8 articles included in the meta-analysis. Results: The results of the analysis of 8 articles showed that aerobic training exercise was effective in improving walking balance in PD patients with a large intervention effect (d = -0.78; CI: -1.00 to -0.55; P <0.001) with a control group comparison. Conclusion: The effectiveness of aerobic exercise in improving walking balance is due to increased physical fitness which has an impact on the cognitive function of executing walking activities in PD patients. Keywords : aerobic exercise, parkinson's disease, walking balance